Extracellular enzyme production in Metarhizium anisopliae isolates - Mustafa, U; Kaur, G (Folia microbiologica, 2009)
Extracellular enzymes produced by Metarhizium anisopliae are believed to play a key role in cuticle hydrolysis. The in-vitro production of cuticle-degrading enzymes, such as chitinase, proteinase, caseinase, lipase and amylase in fourteen isolates of M. anisopliae exhibited significant natural isolate variability. The isolates were also evaluated for chitinase and proteinase enzyme assays in order to quantify the enzyme production. The growth characteristics and colony morphology of the isolates showed variation and few isolates formed sectors and the colonies were either fluffy or powdery. Among the isolates studied, isolate UM2 was found to show good consistence with the results on enzyme measurements as well as the growth characteristics and colony morphology. Such characterization of isolate variability could rationally be used in the selection of isolates for the production of improved myco-pesticides in the integrated pest management programs.
Keywords: enzymy; genetická variace; Genetic Variation; Metarhizium; Animals; Financing, Organized; fungální proteiny; financování organizované; Fungal Proteins; hmyz; Insecta; zvířata; Enzymes